Potential roles of psychological and oxidative stress in insulin resistance: a cohort-based study - Miroslaw Janczura; Jerzy Dropinski; Anna Gielicz; Katarzyna Kotula-Horowitz; Teresa Iwaniec; Andrzej Stanisz; Rafal Rosa; Teresa B. Domagala (Diabetology & Metabolic Syndrome, 2020)
Abstract Background The present study investigated the relationships between psychological stress indices and oxidative stress marker, also when combined with emergent insulin resistance (IR), in the non-diabetic, middle-aged subjects, exposed to frequent/chronic psychological stressors. Methods Cross-sectional data from a cohort of non-diabetic police officers (n = 234; 19F), aged 27–56 years, were used. Plasma inflammatory (CRP, TNF-α), oxidative stress (free 8-iso-prostaglandin F2α; 8-iso-PGF2α) markers, and insulin were measured. The value of homeostasis model assessment of IR index (HOMA-IR) was assumed the threshold value of IR, i.e. 2.04. Free cortisol in urine and perceived stress (psychological stress indices) were also measured. Results In the IR subjects, most biochemical variables, inflammatory markers and urine cortisol were significantly higher, as compared to the non-IR ones. Psychological stress indices were associated with plasma 8-iso-PGF2α [B = 0.139, 95% CI (0.048, 0.230), p = 0.002, and B = 0.007, 95% CI (0.0006, 0.014), p = 0.03; for perceived stress level and cortisol, respectively]. Positive associations were established between plasma 8-iso-PGF2α [B = 0.069, 95% CI (0.016–0.120), p = 0.01] and urine cortisol [B = 0.003, 95% CI (0.0003, 0.005), p = 0.02] with HOMA-IR. Metabolic syndrome, as defined by IDF criteria, was established in 110 study subjects, whereas 136 of them were hypertensive. Waist circumference [B = 0.056, 95% CI (0.039, 0.074), p < 0.0001], and systolic blood pressure [B = 0.009, 95% CI (0.00003, 0.018), p = 0.04] were positively associated with HOMA-IR, whereas the association of HDL cholesterol [B = − 0.597, 95% CI (− 1.139, − 0.055), p = 0.03] was a negative one. Cortisol [OR = 1.007, 95% CI (1.002, 1.012), p = 0.006], and 8-iso-PGF2α [OR = 1.103, 95% CI (1.010, 1.201), p = 0.02] affected the incidence of IR. After adjustment for metabolic syndrome (or its components), age, sex, and current smoking, the effects became non-significant. Out of metabolic syndrome components, waist circumference [OR 4.966, 95% CI (2.29, 10.751), p = 0.00004] and hypertriglyceridemia [OR 1.993, 95% CI (1.063, 3.736), p = 0.03] increased the chance of IR incidence. Conclusions Both psychological stress indices were associated with oxidative stress, but only cortisol with HOMA-IR. In the subjects exposed to frequent/chronic psychological stressors, cortisol and oxidative stress marker affected IR incidence, being statistically attenuated, though, following adjustment for metabolic syndrome, or its components.